من العلامة ملا محمد الرئيس الگلالي إلى الأديب السيد علاءالدين السجادي دراسة وتحقيق - كريم, أ.م. حسين حسن (Sulaimani Journal for Humanities, 2023)
This research is a literary and historical letter written by the famous Kurdish religious scholar Haji Mullah Mohammed Bokani-Gallali, also known as Mullah Mohammed Rais. Sent to the famous Kurdish religious scholar and writer Aladdin Sajadi, The letter is literarily unique and powerful, containing national sentiment, incorporating examples from the Holy Qur'an and the unique poetry of the great Arab poet Mutanabbi - encouraging Sajadi to be more patient and optimistic about the tragedy he has suffered. He encourages that being close to Sheikh Mahmoud Hafid-Maliki at the end of the second decade is his happiness. He showed great respect for Sheikh Mahmoud and his revolution and courage. He also recalls some memories of our school days and respectfully mentions some of their great teachers and scholars.